Analisis Strategi Bisnis Dalam Upaya Meningkatkan Penjualan Produk Usaha Koperasi Mahasiswa UIN Gusdur Pekalongan - Gunawan Aji; Rokhmatus Solekha; Mizanatus Sabillah; Fara Lustiani; Winata Prasetio (FEB Universitas Maritim Semarang, 2023)
Business is always related to how we get profit. This study aims to examine how to process properly in the business world by prioritizing business strategy K.H. UIN student cooperative Abdurrahman Wahid trains students entrepreneurial spirit to develop better human resources. The result of this study are Business Strategy, how student themselves can do business with student cooperatives.